How Much Can We Ask of Collective Agents?. Issue 7 (October 2020) - Collins, Stephanie
Abstract: Are obligations of collective agents—such as states, businesses, and non-profits—ever overdemanding? I argue they are not. I consider two seemingly attractive routes to collective overdemandingness: that an obligation is overdemanding on a collective just if the performance would be overdemanding for members; and that an obligation is overdemanding on a collective just if the performance would frustrate the collective's permissible deep preferences. I reject these. Instead, collective overdemandingness complaints should be reinterpreted as complaints about inability or third-party costs. These are not the same as overdemandingness. Accordingly, we can ask an awful lot of collective agents.